Progressive familial intrahepatic cholestasis type‐3 and multiple sclerosis: lessons from comorbidity - Roberto De Masi; Stefania Orlando; Antonella De Donno (Annals of Clinical and Translational Neurology, 2019)
Abstract The comorbidity between multiple sclerosis (MS) and progressive familial intrahepatic cholestasis type‐3 (PFIC3) has never been described yet. ABCB4 gene encodes the multidrug resistant protein 3 (MDR3) and its mutations induce PFIC3 as well as intrahepatic cholestasis of pregnancy (ICP) and drug‐induced liver injury (DILI). We describe the case of a 32‐year‐old female with MS and PFIC3 who was effectively treated with natalizumab and ursodeoxycholic acid (UCDA), in contrast to glatiramer acetate, dimethylfumarate, and IFNb1a associated with DILI. Our findings clarify the pharmacodynamics of MS therapies and suggest natalizumab plus UDCA as the effective treatment of PFIC3/MS phenotype, unlike the others that should be avoided.